Oxidative Stress Markers Are Associated with a Poor Prognosis in Patients with Pancreatic Cancer - Miguel A. Ortega; Oscar Fraile-Martinez; Leonel Pekarek; Cielo García-Montero; Miguel Angel Alvarez-Mon; Alejandro J. Castellanos; Natalio García-Honduvilla; Julia Buján; Melchor Alvarez-Mon; Miguel A. Sáez; Luis G. Guijarro; Angel Asúnsolo (MDPI AG, 2022)
Pancreatic cancer is a malignancy of rising prevalence, especially in developed countries where dietary patterns and sedentariness favor its onset. This malady ranks seventh in cancer-related deaths in the world, although it is expected to rank second in the coming years, behind lung cancer. The low survival rate is due to the asymptomatic course of the early stages, which in many cases leads to metastases when becoming evident in advanced stages. In this context, molecular pathology is on the way towards finding new approaches with biomarkers that allow a better prognosis and monitoring of patients. So the present study aims to evaluate a series of molecular biomarkers, PARP1, NOX1, NOX2, eNOS and iNOS, as promising candidates for prognosis and survival by using immunohistochemistry. The analysis performed in 41 patients with pancreatic cancer showed a correlation between a high expression of all these components with a low survival rate, with high statistical power for all. In addition, a 60-month longitudinal surveillance program was managed, accompanied by several clinical parameters. The derivative Kaplan-Meier curves indicated a low cumulative survival rate as well. Ultimately, our research emphasized the value of these molecules as survival-associated biomarkers in pancreatic cancer, offering new gates for clinical management.